Enhancing the Quality of Islamic Higher Education through Islamic Consumer Value - Fitriyah, Fitriyah; Mukhlis, Imam; Noviarakhman Zagladi, Arief (Jurnal Ekonomika dan Bisnis Islam, 2023)
The main consumers for educational institutions are students, it is necessary to know the considerations of students in making decisions to study at Islamic Religious Universities (PTKIN). The concept of customer perceived value (CPV) can be applied to research that focuses on muslin consumers by adding Islamic attributes. The purpose of this research is to identify the Islamic value that should be in PTKIN as a strategy to improve its quality. This research uses qualitative research methods. The informants of this research are students of the Faculty of Economics, State Islamic University of Malang, a total of 12 students from 2020sd 2022. Data collection in this study includes direct observation, interviews with informants and documentation studies. Analysis stages include data collection, data reduction, data presentation, data coding. From the results of interviews and then coding, it shows that the concept of customer perceived value can also be applied to college consumers. CPV aspects are summarised in 3 points, namely Islamic Academic, Islamic Value, and Islamic Attribute. This research contributes to university-level decision makers by focusing on these three attributes to be developed into a policy. This research can be further developed by quantitatively testing of these three aspects.